Regulators of Starch Biosynthesis in Cereal Crops - Ruiqing Li; Yuanyuan Tan; Huali Zhang (Molecules, 2021)
Starch is the main food source for human beings and livestock all over the world, and it is also the raw material for production of industrial alcohol and biofuel. A considerable part of the world’s annual starch production comes from crops and their seeds. With the increasing demand for starch from food and non-food industries and the growing loss of arable land due to urbanization, understanding starch biosynthesis and its regulators is essential to produce the desirable traits as well as more and better polymers via biotechnological approaches in cereal crops. Because of the complexity and flexibility of carbon allocation in the formation of endosperm starch, cereal crops require a broad range of enzymes and one matching network of regulators to control the providential functioning of these starch biosynthetic enzymes. Here, we comprehensively summarize the current knowledge about regulatory factors of starch biosynthesis in cereal crops, with an emphasis on the transcription factors that directly regulate starch biosynthesis. This review will provide new insights for the manipulation of bioengineering and starch biosynthesis to improve starch yields or qualities in our diets and in industry.